Problematika Hadits Sebagai Sumber Hukum Islam - Sahid, Syarifuddin (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Hadith is one of the main sources of Islamic law after the Qur'an. However, in its development, hadith faces various problems that affect its validity and application in Islamic law. This article discusses several main problems in the study of hadith, such as authenticity, transmission methods, and its relevance in the context of modern Islamic law. Using a descriptive-qualitative approach, this article attempts to identify the challenges in understanding hadith as a source of law and the solutions that can be offered in the study of hadith science